Book Review: Pembentukan Karakter Melalui Teks-Teks Harta Dalam Amsal 10:1-22:16 - Feriyanto Adolof (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
The book Pembentukan Karakter Melalui Teks-Teks Harta dalam Amsal 10:1–22:16 by Farel Yosua Sualang explores in depth the relationship between wealth and character formation based on biblical wisdom. The primary focus of the book is Proverbs 10:1–22:16, a section containing Solomon’s teachings on the importance of managing wealth wisely. In an increasingly materialistic world, this work offers a theological perspective that wealth is not an ultimate goal but rather a means of reflecting integrity, wisdom, and obedience to God. The author discusses several major themes, including human responses toward wealth, the purpose of wealth in the light of wisdom, the characteristics of wise individuals in managing possessions, and personal evaluations of material ownership. In addition to providing practical applications, the book seeks to correct misinterpretations of Proverbs through an exegetical approach that carefully considers the nature of wisdom literature. One of the major strengths of this book lies in its profound theological analysis, systematic academic methodology, and its relevance to contemporary Christian life. The discussion demonstrates that wealth management is not merely about economic matters but also concerns the moral and spiritual dimensions of human life. Nevertheless, the book still has several limitations. Its highly academic language may be challenging for general readers, while its exclusive focus on Proverbs 10:1–22:16 limits broader exploration of themes of wealth in other biblical texts. Overall, this book makes an important contribution to theological and Christian ethical studies, particularly to understanding the relationship among wealth, character formation, and Christian spirituality.